Proposal for an instructive methodological class in the subject Clinical Propedeutics and medical semiology - Garzón Cutiño, Lisbel (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: the teaching-learning process of the subject of Clinical Propedeutics and medical semiology is a real challenge. Methodological work is the most important activity within the educational system since it contributes to increasing efficiency in teaching work. The objective of the methodological class is to instruct teachers. Aim: make a proposal for an instructive methodological class in the subject Clinical Propedeutics and medical semiology aimed at the use of information and communications technologies. Methods: a qualitative pedagogical research was carried out. The observation of the educational teaching process was carried out in the subject Clinical Propedutics and medical semiology. Systematization, logical historical method and documentary analysis were used as theoretical methods. Results: Proposal for an instructive methodological class in the subject Clinical Propedeutics and medical semiology. Methodological objective: implement strategies aimed at the use of information and communications technologies contributing to the development of the clinical line in the subject Clinical Propedeutics and medical semiology. Conclusions: by offering concrete strategies and practical examples, this proposal encourages innovation in classrooms and creates a more dynamic and effective learning environment.